2013
DOI: 10.1248/cpb.c13-00361
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Tricyclic Lactam Model Compounds of Renieramycin and Saframycin Anticancer Natural Products from Common Intermediate

Abstract: Tricyclic lactam model compounds of the left half (ABC ring) of renieramycin and saframycin anticancer natural products were prepared from common intermediate 6a. Readily available alcohol 6a was converted into enamide 8, and this was followed by transformation into 6b through a hydrobromination reaction in a stereoselective manner. Some diastereomers at C-6 to C-11a of the tricyclic lactam model compounds having several functional groups at C-6 were prepared from 6a or 6b in good yields. We presented also an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Compound was obtained as a colorless prisms by recrystallization from MeOH. trans-32: 1 H-NMR (400 MHz, CD3OD) δ: 7.97 (2H, d, J = 7.9 Hz, Bz-H), 7.59 (1H, t, J = 7.9 Hz, Bz-H), 7.45 (2H, t, J = 7.9 Hz, Bz-H), 6.27 (1H, s, 10-H), 6.13 (1H, dd, J = 9.5, 3.8 Hz, 6-H), 4.81-4.86 (1H, 11a-H overlapped with H2O), 4.75 (1H, dd, J = 11.6, 9.5 Hz, 12-H), 4.60 (1H, dd, J = 11.6, 3.8 Hz, 12-H), 4.34 (1H, d, J = 18.0 Hz, 3-H), 4.23 (1H, d, J = 18.0 Hz, 3-H), 3.20 (2H, d, J = 7.3 Hz, 11-H), 2.50 (3H, s, 2-COCH3), 2.06 (3H, s, 8-CH3); 13 C-NMR (100 MHz, CD3OD) δ: 173.2 (s, 2-COCH3), 169.4 (s, C-1), 168.2 (s, C-14), 165.8 (s, C-4), 157.0 (s, C-9), 153.9 (s, C-7), 134.4 (d, Bz), 132.2 (s, Bz), 131.2 (s, C-10a), 130.7 (d, Bz), 129.6 (d, Bz), 111.4 (s, C-6a), 111.4 (s, C-8), 107.9 (d, C-10), 64.5 (t, C-12), 55.7 (d, C-11a), 50.2 (d, C-6), 46.7 (t, C-3), 32.1 (t, C-11), 27.0 (q, 2-COCH3), 8.7 (q, 8-CH3); IR (KBr): 3410, 3391, 1713, 1659, 1273, 1099 cm -1 ; EIMS m/z (%): 438 (M + , 2), 346 (5), 345 (25), 304 (11), 303 (67), 281 (6), 262 (15), 261 (100), 260 (5), 239 (5), 233 (5), 176 (25), 105 (17); HREIMS: calcd for C23H22N2O7 438.1427; found 438.1428. cis-32: mp 243-245 °C (MeOH); 1 H-NMR (400 MHz, CD3OD) δ: 7.87 (2H, br d, J = 7.8 Hz, Bz-H), 7.56 (1H, br t, J = 7.8 Hz, Bz-H), 7.41 (2H, br t, J = 7.8 Hz, Bz-H), 6.35 (1H, s, 10-H), 6.12 (1H, dd, J = 7.9, 4.7 Hz, 6-H), 4.84 (1H, d, J = 16.8 Hz, 3-H), 4.50 (1H, dd, J = 10.9, 7.9 Hz, 12-H), 4.33 (1H, dd, J = 10.9, 4.7 Hz, 12-H), 4.30 (1H, dd, J = 12.1, 5.0 Hz, 11a-H), 3.89 (1H, d, J = 16.8 Hz, 3-H), 3.25 (1H, dd, J = 15.5, 12.1 Hz, 11-H), 3.07 (1H, dd, J = 15.5, 5.0 Hz, 11-H), 2.49 (3H, s, 2-COCH3), 2.07 (3H, s, 8-CH3); 13 C-NMR (100 MHz, CD3OD) δ: 172.4 (s, 2-COCH3), 170.7 (s, C-1), 168.9 (s, C-14), 168.1 (s, C-4), 157.2 (s, C-9), 153.8 (s, C-7), 134.4 (d, Bz), 133.0 (s, C-10a), 131.1 (s, Bz), 130.6 (d, Bz), 129.5 (d, Bz), 112.1 (s, C-6a), 111.4 (s, C-8), 107.5 (d, C-10), 66.6 (t, C-12), 57.8 (d, C-11a), 50.2 (d, C-6), 46.3 (t, C-3), 30.1 (t, C-11), 26.9 (q, 2-COCH3), 8.8 (q, 8-CH3); IR (KBr):3383, 3366, 2924, 1717, 1678, 1368, 1271, 1198, 1099 cm -1 ; EIMS m/z (%): 438 (M + , 1), 346(6), 345(12), 305(14), 304 (54), 303 (100), 263 (5), 262(18), 261 (31), 177(16), 176 (33), 105(13), 77 (5); HREIMS m/z: calcd for C23H22N2O7 438.1427; found 438.1422; Anal. Calcd for C23H22N2O7:C, 63.01; H, 5.06; N, 6.39.…”
mentioning
confidence: 99%
“…Compound was obtained as a colorless prisms by recrystallization from MeOH. trans-32: 1 H-NMR (400 MHz, CD3OD) δ: 7.97 (2H, d, J = 7.9 Hz, Bz-H), 7.59 (1H, t, J = 7.9 Hz, Bz-H), 7.45 (2H, t, J = 7.9 Hz, Bz-H), 6.27 (1H, s, 10-H), 6.13 (1H, dd, J = 9.5, 3.8 Hz, 6-H), 4.81-4.86 (1H, 11a-H overlapped with H2O), 4.75 (1H, dd, J = 11.6, 9.5 Hz, 12-H), 4.60 (1H, dd, J = 11.6, 3.8 Hz, 12-H), 4.34 (1H, d, J = 18.0 Hz, 3-H), 4.23 (1H, d, J = 18.0 Hz, 3-H), 3.20 (2H, d, J = 7.3 Hz, 11-H), 2.50 (3H, s, 2-COCH3), 2.06 (3H, s, 8-CH3); 13 C-NMR (100 MHz, CD3OD) δ: 173.2 (s, 2-COCH3), 169.4 (s, C-1), 168.2 (s, C-14), 165.8 (s, C-4), 157.0 (s, C-9), 153.9 (s, C-7), 134.4 (d, Bz), 132.2 (s, Bz), 131.2 (s, C-10a), 130.7 (d, Bz), 129.6 (d, Bz), 111.4 (s, C-6a), 111.4 (s, C-8), 107.9 (d, C-10), 64.5 (t, C-12), 55.7 (d, C-11a), 50.2 (d, C-6), 46.7 (t, C-3), 32.1 (t, C-11), 27.0 (q, 2-COCH3), 8.7 (q, 8-CH3); IR (KBr): 3410, 3391, 1713, 1659, 1273, 1099 cm -1 ; EIMS m/z (%): 438 (M + , 2), 346 (5), 345 (25), 304 (11), 303 (67), 281 (6), 262 (15), 261 (100), 260 (5), 239 (5), 233 (5), 176 (25), 105 (17); HREIMS: calcd for C23H22N2O7 438.1427; found 438.1428. cis-32: mp 243-245 °C (MeOH); 1 H-NMR (400 MHz, CD3OD) δ: 7.87 (2H, br d, J = 7.8 Hz, Bz-H), 7.56 (1H, br t, J = 7.8 Hz, Bz-H), 7.41 (2H, br t, J = 7.8 Hz, Bz-H), 6.35 (1H, s, 10-H), 6.12 (1H, dd, J = 7.9, 4.7 Hz, 6-H), 4.84 (1H, d, J = 16.8 Hz, 3-H), 4.50 (1H, dd, J = 10.9, 7.9 Hz, 12-H), 4.33 (1H, dd, J = 10.9, 4.7 Hz, 12-H), 4.30 (1H, dd, J = 12.1, 5.0 Hz, 11a-H), 3.89 (1H, d, J = 16.8 Hz, 3-H), 3.25 (1H, dd, J = 15.5, 12.1 Hz, 11-H), 3.07 (1H, dd, J = 15.5, 5.0 Hz, 11-H), 2.49 (3H, s, 2-COCH3), 2.07 (3H, s, 8-CH3); 13 C-NMR (100 MHz, CD3OD) δ: 172.4 (s, 2-COCH3), 170.7 (s, C-1), 168.9 (s, C-14), 168.1 (s, C-4), 157.2 (s, C-9), 153.8 (s, C-7), 134.4 (d, Bz), 133.0 (s, C-10a), 131.1 (s, Bz), 130.6 (d, Bz), 129.5 (d, Bz), 112.1 (s, C-6a), 111.4 (s, C-8), 107.5 (d, C-10), 66.6 (t, C-12), 57.8 (d, C-11a), 50.2 (d, C-6), 46.3 (t, C-3), 30.1 (t, C-11), 26.9 (q, 2-COCH3), 8.8 (q, 8-CH3); IR (KBr):3383, 3366, 2924, 1717, 1678, 1368, 1271, 1198, 1099 cm -1 ; EIMS m/z (%): 438 (M + , 1), 346(6), 345(12), 305(14), 304 (54), 303 (100), 263 (5), 262(18), 261 (31), 177(16), 176 (33), 105(13), 77 (5); HREIMS m/z: calcd for C23H22N2O7 438.1427; found 438.1422; Anal. Calcd for C23H22N2O7:C, 63.01; H, 5.06; N, 6.39.…”
mentioning
confidence: 99%
“…20−23 To date, renieramycins A−Y isolated from such sponges have been characterized and become target molecules of interest for synthetic studies 24−37 and biological investigations as the promising anticancer agents. 6,8,9,14,24,34,38 Renieramycin M (1), the most prominent compound in this category, is a bistetrahydroisoquinolinequinone that was isolated as a preeminent alkaloid from the potassium cyanidepretreated methanolic extract of the blue sponge Xestospongia sp., which has been collected in Thailand 13 and the Philippines. 15 Regarding our ongoing research toward the development of new anticancer agents from marine tetrahydroisoquinoline alkaloids, including renieramycins and ectinascidins, the naturally derived renieramycins such as renieramycin M (1), renieramycin E, and renieramycin T (2), a renieramycin− ecteinascidin hybrid structure, showed strong cytotoxicity with IC 50 values in the nanomolar range toward various cancer cell lines, including breast (T47D), colon (HCT116 and DLD1), lung (QG56 and H460), pancreatic (AsPC1), and prostate (DU145) human carcinomas.…”
mentioning
confidence: 99%
“…Regarding their structural complexity and diversity, these marine-derived molecules are capable of interacting with numerous biomolecular targets to either inhibit or promote specific biological functions against various types of cancer cell lines. Renieramycins, marine alkaloids classified into the tetrahydroisoquinoline family, have been isolated from various marine organisms, including sponges in the genera Reniera , , Xestospongia , Cribrochalina , , and Neopetrosia. Moreover, several renieramycin-type alkaloids have also been obtained from a sponge-eating nudibranch, Jorunna funebris . To date, renieramycins A–Y isolated from such sponges have been characterized and become target molecules of interest for synthetic studies and biological investigations as the promising anticancer agents. ,,,,,, Renieramycin M ( 1 ), the most prominent compound in this category, is a bistetrahydro­isoquinolinequinone that was isolated as a preeminent alkaloid from the potassium cyanide-pretreated methanolic extract of the blue sponge Xestospongia sp., which has been collected in Thailand and the Philippines …”
mentioning
confidence: 99%
“…The most prominent compound in this group is renieramycin M isolated from the potassium cyanide pretreated methanolic extract of the blue sponge Xestospongia sp., which has been collected in Thailand and the Philippines [26,27]. Besides from renieramycin M, renieramycins A-Y are isolated from many species of sponges and become target molecules for synthetic studies and biological researches as the anticancer agents [108][109][110][111][112][113][114][115][116][117][118]. Many evidences showed that renieramycins had a strong cytotoxicity against various cancer cells, including breast (T47D), colon (HCT116 and DLD1), lung (QG56 and H460), pancreatic (AsPC1), and prostate (DU145) human carcinomas [23,26,36,114] In 2009, Charupant found that renieramycin M and their derivatives had anti-proliferative activities against breast (MDA-MB-435), and colon (HCT116) cancer cells with a very low IC50 [119].…”
Section: Renieramycinsmentioning
confidence: 99%